MELACAK KONSEP DASAR KECERDASAN EMOSIONAL - Nasril Nasril (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2018)
Emotional intelligence is the ability to recognize, process, and control emotions so that a person is able to respond positively to any condition that stimulates emotion. Emotional and social skills, will be better able to overcome various problems that arise during the process of development towards adult humans. not only that, with their emotional and social skills, a person is better able to overcome the challenges of emotional challenges in modern life. The success of one's life is more determined by emotional intelligence, namely aspects related to personality, which consists of four main elements, namely: First, a person's ability to understand and motivate his potential; Second, having a high sense of empathy towards others; Third, happy to even encourage successful subordinates, without feeling themselves threatened; Fourth, is assertive, that is skillful in conveying thoughts and feelings well, straightforwardly, and clearly without having to offend others. Various studies in the field of psychology have proven that someone who has high emotional intelligence is a person who is happy, confident, popular, and more successful with others, can manage stress, and have good mental health.